The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0101-81752003000400010
|View full text |Cite
|
Sign up to set email alerts
|

Reprodução das aves marinhas nas ilhas costeiras de Santa Catarina, Brasil

Abstract: Estudos enfocando a reprodução das aves marinhas no litoral brasileiro são raros quando comparados aos das espécies continentais. Em função da infraestrutura com que conta a maioria dos ornitólogos marinhos para enfrentar as adversidades do mar, além da ausência de atracadouros para o reabastecimento da equipe, abrigos e a morosidade na liberação das permissões de permanência, comprometem o acesso e monitoramento periódico das colônias de aves nas ilhas de nidificação.Mesmo assim, alguns pesquisadores têm cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 2 publications
0
21
1
12
Order By: Relevance
“…Similarly, in Argentina over 75% of Cabot's Terns nest in any given year at a few of ten potential breeding sites located at Punta León and in a small coastal sector in the north of Golfo San Jorge, Chubut (Yorio & Efe 2008). The reported reproductive period of Cabot's Terns on the Santa Catarina coast is May to October (Soares & Schiefler 1995, Branco 2003a). Our research found timing similar to that described by Efe et al (2000) as from May to September on the islands of Espírito Santo, which differs from the period (March-October) cited for the coast of Rio de Janeiro (Sick andLeão 1965, Sick 1997), for the coast of Paraná (June to September -Krul 2004), for the coast of São Paulo (May to August -Campos et al 2004), and for the coast of Argentina (November to February - Scolaro et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in Argentina over 75% of Cabot's Terns nest in any given year at a few of ten potential breeding sites located at Punta León and in a small coastal sector in the north of Golfo San Jorge, Chubut (Yorio & Efe 2008). The reported reproductive period of Cabot's Terns on the Santa Catarina coast is May to October (Soares & Schiefler 1995, Branco 2003a). Our research found timing similar to that described by Efe et al (2000) as from May to September on the islands of Espírito Santo, which differs from the period (March-October) cited for the coast of Rio de Janeiro (Sick andLeão 1965, Sick 1997), for the coast of Paraná (June to September -Krul 2004), for the coast of São Paulo (May to August -Campos et al 2004), and for the coast of Argentina (November to February - Scolaro et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Its range extends from the southern USA, in the Caribbean along the coasts of Colombia and Venezuela and in Surinam, Brazil and Uruguay as far south as Puerto Deseado in Argentina (Escalante 1973, Shealer 1999, Barbieri & Paes 2008. Generally they form dense colonies, with nests located about 50cm apart, and have a clutch size of only one egg, which may present one of three color patterns based on number/color of spots per egg , Branco 2003a.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O tamanho dos ovos colocados nos ninhos de gaivotas e trinta-réis, tendem a diminuir com a ordem de postura (PARSONS 1970, BRANCO 2003. O comprimento médio, largura e massa dos ovos apresentaram pequenas oscilações entre os sítios de nidificação, sendo idênticos aos registrados por YU & HAHM (1997) na Província de Kyungnam (Coréia).…”
Section: Discussionunclassified